Bio-filtration of trichloroethylene using diazotrophic bacterial community - Shukla A.K.; Vishwakarma P.; Singh R.S.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
Biodegradation of TCE was studied in a biofilter packed with wood charcoal and inoculated with diazotrophic bacterial community isolated from local soil. Steady state TCE removal efficiencies higher than 85% were observed up to inlet load of 2.866 g m-3 h-1. The maximum elimination capacity of 5.31 gm-3 h-1 was observed at an inlet load of more than 7.90 g m-3 h-1. The biofilter was sensitive to fluctuations in the process conditions but could easily recover its performance after 10 days shutdown. Almost constant and small pressure drop per unit length and very negligible compaction was observed during the whole experimental period. The molecular analyses such as RT-PCR and gene sequencing revealed the presence of functionally active Azospirillum species in the biofilm. © 2009 Elsevier Ltd. All rights reserved.